Pedo-sedimentary constituents as paleoenvironmental proxies in the Sudano-Sahelian belt during the Late Quaternary (southwestern Chad Basin). (1st July 2018) - Diaz, Nathalie; Dietrich, Fabienne; Sebag, David; King, Georgina E.; Valla, Pierre G.; Durand, Alain; Garcin, Yannick; de Saulieu, Geoffroy; Deschamps, Pierre; Herman, Frédéric; Verrecchia, Eric P.
Abstract: Climate and environmental changes since the Last Glacial Maximum in the tropical zone of West Africa are usually inferred from marine and continental records. In this study, the potential of carbonate pedo-sedimentary geosystems, i.e. Vertisol relics, to record paleoenvironmental changes in the southwestern part of Chad Basin are investigated. A multi-dating approach was applied on different pedogenic organo-mineral constituents. Optically stimulated luminescence (OSL) dating was performed on the soil K-rich feldspars and was combined with radiocarbon dating on both the inorganic ( 14 Cinorg ) and organic carbon ( 14 Corg ) soil fractions. Three main pedo-sedimentary processes were assessed over the last 20 ka BP: 1) the soil parent material deposition, from 18 ka to 12 ka BP (OSL), 2) the soil organic matter integration, from 11 cal ka to 8 cal ka BP ( 14 Corg ), and 3) the pedogenic carbonate nodule precipitation, from 7 cal ka to 5 cal ka BP ( 14 Cinorg ). These processes correlate well with the Chad Basin stratigraphy and West African records and are shown to be related to significant changes in the soil water balance responding to the evolution of continental hydrology during the Late Quaternary. The last phase affecting the Vertisol relics is the increase of erosion, which is hypothesized to be due to a decrease of the vegetation cover triggered by (i) the onset of drier conditions, possibly strengthened by (ii) anthropogenic pressure. Archaeological data from Far North Cameroon and northern Nigeria, as well as sedimentation times in Lake Tilla (northeastern Nigeria), were used to test these relationships. The increase of erosion is suggested to possibly occur between c. 3 cal ka and 1 cal ka BP. Finally, satellite images revealed similar geosystems all along the Sudano-Sahelian belt, and initial 14 Cinorg ages of the samples collected in four sites gave similar ages to those reported in this study. Consequently, the carbonate pedo-sedimentary geosystems are valuable continental paleoenvironmental archives and soil water balance proxies of the semiarid tropics of West Africa. Highlights: This work aims at showing the potential of pedo-sedimentary archives as paleo-environmental records. We used a multi-dating approach on different pedo-sedimentary components, and resulting ages represent precise pedo-sedimentary processes that are not overlapping through time. We compared our results with existent archaeological and paleo-climatic archives, and we showed that pedo-sedimentary processes are linked to soil water balance changes and are thus proxies of continental hydrological changes, in turn linked to climate and/or anthropic activities. The pedo-sedimentary archives also occur in other areas along the Sudano-Sahelian belt, primary results show their real potential at this scale for a region lacking of data in the reconstructions due to low preservations of the records.